Arctigenin Inhibits Adipogenesis by Inducing AMPK Activation and Reduces Weight Gain in High‐Fat Diet‐Induced Obese Mice. Issue 9 (26th May 2016) - Han, Yo‐Han; Kee, Ji‐Ye; Park, Jinbong; Kim, Hye‐Lin; Jeong, Mi‐Young; Kim, Dae‐Seung; Jeon, Yong‐Deok; Jung, Yunu; Youn, Dong‐Hyun; Kang, JongWook; So, Hong‐Seob; Park, Raekil; et al.
ABSTRACT: Although arctigenin (ARC) has been reported to have some pharmacological effects such as anti‐inflammation, anti‐cancer, and antioxidant, there have been no reports on the anti‐obesity effect of ARC. The aim of this study is to investigate whether ARC has an anti‐obesity effect and mediates the AMP‐activated protein kinase (AMPK) pathway. We investigated the anti‐adipogenic effect of ARC using 3T3‐L1 pre‐adipocytes and human adipose tissue‐derived mesenchymal stem cells (hAMSCs). In high‐fat diet (HFD)‐induced obese mice, whether ARC can inhibit weight gain was investigated. We found that ARC reduced weight gain, fat pad weight, and triglycerides in HFD‐induced obese mice. ARC also inhibited the expression of peroxisome proliferator‐activated receptor gamma (PPARγ) and CCAAT/enhancer‐binding protein alpha (C/EBPα) in in vitro and in vivo. Furthermore, ARC induced the AMPK activation resulting in down‐modulation of adipogenesis‐related factors including PPARγ, C/EBPα, fatty acid synthase, adipocyte fatty acid‐binding protein, and lipoprotein lipase. This study demonstrates that ARC can reduce key adipogenic factors by activating the AMPK in vitro and in vivo and suggests a therapeutic implication of ARC for obesity treatment. J. Cell. Biochem. 117: 2067–2077, 2016. © 2016 Wiley Periodicals, Inc. Abstract : ARC induced the AMPK activation resulting in down‐modulation of adipogenesis‐related factors including PPARγ, C/EBPα, fatty acid synthase, adipocyte fatty acid‐binding protein, and lipoprotein lipase. This study demonstrates that ARC can reduce key adipogenic factors by activating the AMPK in vitro and in vivo.